Ectopic junctional epithelium adhered to the buccal crown surface of an upper central incisor. Issue 1 (April 2020) - Nakamura, Masako Toda; Oka, Kyoko; Harada, Hana; Ogata, Kayoko; Matsuo, Satoru; Rikitake, Mihoko; Ohki, Shirabe; Kumagai, Tetsuya; Kato, Yoko; Baba, Atsuko; Ozaki, Masao
Abstract: A girl attended our clinic with inflammation of the marginal gingiva. The surfaces of central incisors had severe enamel defects caused by trauma to the primary incisors. Swollen but non-ulcerated gingiva was present on the surface of the left central incisor. The gingival mass was surgically removed. Immunohistochemical analyses revealed that the resected mass included epithelial tissue expressing odontogenic ameloblast-associated protein (ODAM), which is a marker of junctional epithelium. It was likely ectopic junctional epithelium that had formed due to disorganization of the enamel organ during development caused by dental trauma to the primary incisors.